Produktion - Distribution - Ökonomie. Siedlungs- und Wirtschaftsmuster der Latènezeit - Mölders, Doreen (2011)
The article reports on a conference on the economic history of the Latène period of the European Iron Age, held in Otzenhausen, Germany, from November 28-30, 2011. Topics discussed included theories of economy and society during this era, particularly that of Austrian economist Karl Polanyi, economic archaeology research, and the trade networks of traditional societies.
History; Archaeology
Keywords: Europe; LA Tene period; POLANYI; Karl; 1886-1964; TO 500; archaeology research; commerce; congresses; economic history; history; iron age; traditional societies